Differential immune signatures in the tumor microenvironment are associated with colon cancer racial disparities. (9th February 2021) - Curran, Thomas; Sun, Zequn; Gerry, Brielle; Findlay, Victoria J.; Wallace, Kristin; Li, Zihai; Paulos, Chrystal; Ford, Marvella; Rubinstein, Mark P.; Chung, Dongjun; Camp, E. Ramsay
Abstract: Background: Disparities in colon cancer (CC) outcomes may be due to a more aggressive phenotype in African American patients in the setting of a decreased tumor immunity, though the precise mechanism for this result has not been well elucidated. To explore the molecular factors underlying CC disparities, we compared the immunogenomic signatures of CC from African American and European American patients. Methods: We identified all CC patients from the publicly available Cancer Genome Atlas for whom race and survival data are available. Immunophenotype signatures were established for African American and European American patients. Comparisons were made regarding survival and a multivariable linear regression model was created to determine the association of immune cellular components with race. Differential gene expression was also assessed. Results: Of the 254 patients identified, 58 (23%) were African American and 196 (77%) were European American. African American patients had a decreased progression free survival ( p  = 0.04). Tumors from African American patients displayed a reduced fraction of macrophages and CD8 + T cells and an increased fraction of B cells compared with tumors from European Americans. Differences persisted when controlling for sex, age, and disease stage. Immunostimulatory and immunoinhibitory gene profiles including major histocompatibility complex expression differed by race. Conclusions: Differences in the tumor immune microenvironment of African American as compared to European American CC specimens may play a role in the survival differences between the groups. These differences may provide targeted therapeutic opportunities. Abstract : We uncovered key molecular factors underlying racial disparities in African American versus European American patients. Immunogenomic signatures in these patient cohorts were identified using a publicly available tumor repository and robust bioinformatic tools. Significant differences in gene expression were found in the tumor microenvironment which may underlie key clinical differences in these patients and reveal new therapeutic targets to effective treat all patients in the future.